Circuit training exercise model through the explosive power of the leg muscles of badminton extracurricular players - Rian Febriansyah; Noviria Sukawati; I Bagus Endrawan; Arif Hidayat; Rian Febriansyah; Noviria Sukawati; I Bagus Endrawan; Arif Hidayat (Pendidikan Jasmani, Kesehatan, dan Rekreasi Universitas Nahdlatul Ulama Sunan Giri, 2026)
The explosiveness of the leg muscles is an important component in supporting the performance of badminton athletes, especially for students who are members of extracurricular activities. This study aims to develop and test the effectiveness of circuit training models in increasing the explosiveness of leg muscles of high school badminton extracurricular students in Palembang City. The method used is research and development (Research and Development) involving expert validation and field trials. The validation results showed that the developed exercise model scored an average of 73.75% from academics, practitioners, and movement experts, which was included in the good category and worth testing. The small group trial at SMAN 8 Palembang obtained a result of 94.67%, while the large group trial at SMAN 9 Palembang showed a score of 92.5%. These results indicate that the circuit training model is very effective in increasing the explosive power of the leg muscles of high school badminton players. The conclusion of the circuit training model has proven to be effective and very good in increasing the explosiveness of the leg muscles of extracurricular badminton students. Practice model suggestions can be widely implemented by coaches or sports teachers as an alternative to physical exercise in badminton extracurricular activities in schools, as well as further research to test the effectiveness at different levels of education.